#TITLE_ALTERNATIVE# - APRILIA (NIM : 15010025), BELLA
Land transportation's main facility is pavement structure. The roads in Indonesia can be classified into 4 distinct categories, which is; national, provincial, regional, and city roads. Only 33.794 kilometers or 63% of provincial roads are in sound condition. The main factor causing high rate of degradation of pavement structure in Indonesia is because of the high variety of climate condition, excessive traffic load (overloading), and unsuitable method used in design and rehabilitation. There are 3 main approach in designing and maintaining pavement structure which is; empirical, analytical/mechanical, and mechanical-empirical. Empirical pavement design is done using Pd T-01-2002-B Pedoman Perencanaan Tebal Perkerasan Lentur (Bina Marga), analytical/mechanical using the Nottingham 1984 method, and mechanical-empirical using AASHTO 2008 (MEPDG). With the MEPDG, a mechanical or analytical approach is done by calculating the effect of climate and traffic load of various land transportation, while an empirical approach is done by inspecting the relationship between critical condition of pavement structure according to various parameters and its existing condition. MEPDG also includes different input levels for design elements, so the designer can choose suitable levels according to availability of data, tools, and the designer‟s skill. To implement the MEPDG manual effectively, it is therefore sensible to do an analysis of its various aspects. According to AASHTO 2008, elements in flexible pavement design includes; climate, traffic, material properties, geometric, structural analysis, and determination of design. AASHTO 2008 (MEPDG) structure analysis is done by referring to 4 distress parameter or performance indicator for HMA-sufaced pavement, which is; rut depth, load related cracking, non-load related cracking, and the International Roughness Index (IRI). For comparison, calculation of pavement design is done for 3 types of traffic volume, which is light, medium, and heavy loads, each type representing 500.000, 5.000.000, and 25.000.000 standard axle-load consecutively. Result from pavement evaluation using MEPDG is smoothness or IRI, pavement thickness is an input parameter that is iterated. The resulting calculation and analysis shows that AASHTO 2008 (MEPDG) yields optimum pavement thickness for all traffic volumes on every pavement layers (HMA-surfaced pavement, subbase, base and subgrade).